Proceedings of the 41st ACM Technical Symposium on Computer Science Education 2010
DOI: 10.1145/1734263.1734432
|View full text |Cite
|
Sign up to set email alerts
|

Does studio-based instruction work in CS 1?

Abstract: Given the increasing importance of communication, teamwork, and critical thinking skills in the computing profession, we believe there is good reason to provide students with increased opportunities to learn and practice those skills in undergraduate computing courses. Toward that end, we have been exploring studio-based instructional methods, which have been successfully employed in architecture and fine arts education for over a century. We have developed an adaptation of studio-based instruction for computi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…There is an iterative process of inquiry and critique within an interactive studio space, where students work with experts who use prompts and discussion to guide the process. This approach has been adopted in settings as varied as mathematics, chemistry, engineering, and computer programming (Hundhausen, Agrawal, Fairbrother, & Trevisan, 2010). However, there is much less research on the effectiveness of studio-based learning; most studies have reviewed the methods only qualitatively.…”
Section: Education and Training In Cpsmentioning
confidence: 99%
“…There is an iterative process of inquiry and critique within an interactive studio space, where students work with experts who use prompts and discussion to guide the process. This approach has been adopted in settings as varied as mathematics, chemistry, engineering, and computer programming (Hundhausen, Agrawal, Fairbrother, & Trevisan, 2010). However, there is much less research on the effectiveness of studio-based learning; most studies have reviewed the methods only qualitatively.…”
Section: Education and Training In Cpsmentioning
confidence: 99%
“…Several studies have explored ways to enrich student attitudes, often with the intention of improving some aspect of course 'health' or the student experience. These interventions include collaborative scaffolding [194], problem-based learning [208], peer tutoring [220], pedagogical code review [282], facilitated e-learning [365], and peer instruction [731].…”
Section: Sentimentmentioning
confidence: 99%
“…This approach emphasises evaluation and communication in the design of a solution, and appears to be more effective when supported by a visualisation tool [289]. Students using a studio-based approach had higher self-efficacy than those in a more traditional classroom environment and were more favourably disposed towards peer learning, but both environments resulted in similar levels of content knowledge in final exams [282]. A three-year case study of studio-based learning reported that students enjoyed the social aspect of studio learning and found its open-ended nature highly engaging [541].…”
Section: Exploratorymentioning
confidence: 99%
“…Table 7 shows the subcategories in this category and the corresponding number of papers published in each decade. Papers in the Other subcategory included topics such as peer code review, studiobased instruction (which includes pedagogical code review) [22], POGIL [20], and group projects. As can be seen in Figure 2, interest in this area has risen dramatically since the turn of the century.…”
Section: Toolsmentioning
confidence: 99%